EDUCATION 4.0:: REFLECTING ON THE USE OF TECHNOLOGIES IN THE TEACHING PRACTICE OF ELEMENTARY TEACHERS - EARLY YEARS - Laryssa de Oliveira Agra, Kamila (Revista Gênero e Interdisciplinaridade, 2021)
This work seeks to understand the new changes in the globalized world and how this happens within the education system, which brings with it new teaching approaches with hybrid teaching and the inverted school, which are proposals that make use of active technologies in their practice. In this way, students are exposed to more dynamic and interactive classes where skills such as creativity and critical sense are awakened in them, in this model the student becomes an active protagonist and learns in a meaningful way. An exploratory quantitative research was carried out, with analytical-descriptive guidance, through semi-structured interviews with open and closed questions. The subjects are teachers from public and private schools in the city of Caruaru - PE. Respondents considered that when faced with a situation where the use of active technologies is fully required, as was the case in this year of 2020 due to COVID-19, this is still challenging, and they have not received training in this area, having to seek training on its own. The suggested measures for this to be improved is to promote more reflection on the subject “active technologies in school practice”, developing training and specific training actions in technological areas, making use of new teaching modalities, reviewing the roles of teachers, students , as well as the physical structure of schools that can promote more social interaction, and of the school institution as a whole